Chiral Pool-Based Synthesis of Naphtho-Fused Isocoumarins - Raza, Abdul Rauf; Saddiqa, Aisha; Cakmak, Osman (WILEY-BLACKWELL, 2015)
A variety of chiral derivatives of benzo[d]naphtho[1,2-b]pyran-6-one were prepared in a single step by Et3N-mediated condensation of homophthalic anhydride with different derivatives of (S)-amino acid chlorides at -5 degrees C by employing a chiral pool methodology. Chirality 27:951-957, 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: isocoumarin; benzo[d]naphtho[1; 2-b]pyran-6-one; homophthalic anhydride; amino acids; CLINICAL-PHARMACOLOGY; DRUG-ACTION; BIOSYNTHESIS; ACIDS; Pharmacology & Pharmacy; Chemistry